High-resolution geochemical records of extreme drought in southeastern Africa during the past 7000 years. (15th May 2020) - Humphries, Marc; Green, Andrew; Higgs, Caldin; Strachan, Kate; Hahn, Annette; Pillay, Letitia; Zabel, Matthias
Abstract: The magnitude and frequency of extreme events is projected to increase under future climate change and understanding the major drivers of global climate variability is dependent on the development of detailed records from critical regions. Subtropical Africa is known to have undergone phases of significant change resulting from variations in broad-scale atmospheric and oceanic circulation patterns, but the nature and cause for these variations remain intensely debated. Here we present a highly resolved sedimentary record from the eastern margin of South Africa to reconstruct hydroclimate in southeast Africa over the past 7000 years. Stratigraphic and inorganic proxies preserve a highly sensitive record that document dramatic shifts in moisture balance, with phases of severe drought recorded at 4700–4200 and 3700–2600 cal yr BP. We suggest that pronounced hydroclimate variability observed in the Mkhuze record was likely triggered by changes in the activity of El Niño-Southern Oscillation (ENSO), which acted to control the transport of moisture from the Indian Ocean across southeast Africa. We show that rapid shifts in moisture availability were a characteristic feature of mid-late Holocene climate across the summer rainfall region of southern Africa, with these events broadly anti-phased with hydroclimatic shifts in East Africa and northwest Madagascar. These findings suggest that evaluating drought frequency, ecological risk and food security within the region is likely to be closely tied to ENSO and its response to future global warming. Highlights: We present a new highly-resolved hydroclimate record from southeast Africa. Severe episodes of aridity recorded at 4700–4200 and 3700–2600 cal yr BP. Instability a feature of Holocene climate across subtropical southern Africa. Abrupt shifts likely triggered by increases in El Niño frequency.